Green Turning Brown – Domain Engineering for Social and Health Services in Finland - Reima Suomi; Pirkko Nykänen; Tapio Vepsäläinen; Riina Hiltunen (Netherlands, 2022)
Being able to design information systems to an untouched domain, without the burden of existing information systems, especially legacy systems, is often seen as a dream of most information system professionals.  Uncharted domains are anyway scarce, and often such greenfield projects turn into brownfield projects, also to projects where existing structures severely constrain the development of new systems.  In this article we discuss the concepts of greenfield and brownfield domain engineering and software development, and reflect their possible messages to the re-engineering of the Finnish health- and social care ecosystem currently under way. In our fieldwork we could identify a lot of need and wish for greenfield domain engineering in the Finnish health- and social services delivery.  As well we found a lot of brownfield elements inhibiting change. Our proposal for the future is a ecosystem approach, where new and established elements could live together in a self-governed balance.
MEDINFO 2017: Precision Healthcare through Informatics